Pengambilan Keputusan Studi Lanjut Siswa SMK Ditinjau dari Parent Attachment dan Konsep Diri - Rahma, Zuyyina; Raharjo, Trubus (Jurnal Simki Pedagogia, 2026)
This study aims to determine the relationship between parent attachment and self-concept with decision-making for further studies in vocational high school students. This study uses a quantitative method. Participants in this study were 122 students of class XII of vocational high school with a sampling technique using quota sampling. The scales used were the parent attachment scale, self-concept scale, and decision-making scale. The correlation coefficient of the three variables rx12y is 0.423 (p <0.01) so there is a very significant relationship between parent attachment and self-concept with decision-making with an effective contribution of 17.9%. Therefore, the major hypothesis in this study is that there is a relationship between parent attachment and self-concept with decision-making is accepted. The results of the analysis of the parent attachment variable with decision-making show rx1y of 0.381 (p > 0.01) and an effective contribution of 14.5%. Therefore, there is a positive relationship between parent attachment and decision-making, the first hypothesis is accepted. While the results of the analysis of the self-concept variable with decision-making show rx2y of 0.327 (p <0.01) with an effective contribution of 10.7%. So there is a positive relationship between self-concept and decision making, the second hypothesis is accepted.